2017
DOI: 10.1080/10428194.2017.1349905
|View full text |Cite
|
Sign up to set email alerts
|

Updating survival estimates in patients with chronic lymphocytic leukemia or small lymphocytic lymphoma (CLL/SLL) based on treatment-free interval length

Abstract: We hypothesized that the length of treatment-free survival following (a) initial diagnosis and (b) first-line treatment would be associated with improved subsequent five-year relative survival (RS5) in patients with chronic lymphocytic leukemia or small lymphocytic lymphoma (CLL/SLL). 19,879 patients incident CLL/SLL cases (median age = 76 years) were identified from SEER-Medicare. RS5 improved from 0.73 (95% CI: 0.72, 0.74) at diagnosis to 0.81 (95% CI: 0.80, 0.82) at year 1 and 0.89 (95% CI: 0.83, 0.96) at y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Five-year RS estimated at diagnosis was higher in our study (85; 95% CI, 84–87%), as compared to the earlier series in the Netherlands (72; 95% CI, 71–73%) 3 and the U.S. study (82; 95% CI, 81–83%) 4 . Akin to previous studies in FL, we observed a slight increase in CRS during follow-up that was less pronounced as compared to other types of lymphomas 3 , 4 , 9 , 10 . The increase in CRS among patients with FL is most likely accounted for by improvements in FL management during sequent periods, especially the implementation of rituximab across various lines of therapy 11 , 12 .…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Five-year RS estimated at diagnosis was higher in our study (85; 95% CI, 84–87%), as compared to the earlier series in the Netherlands (72; 95% CI, 71–73%) 3 and the U.S. study (82; 95% CI, 81–83%) 4 . Akin to previous studies in FL, we observed a slight increase in CRS during follow-up that was less pronounced as compared to other types of lymphomas 3 , 4 , 9 , 10 . The increase in CRS among patients with FL is most likely accounted for by improvements in FL management during sequent periods, especially the implementation of rituximab across various lines of therapy 11 , 12 .…”
supporting
confidence: 82%
“…The discrepancy might stem from the inclusion of patients in population-based series who are not eligible for trials and who achieved and did not achieve EFS24, thereby possibly averaging of the prognostic effect of EFS24. Nonetheless, an increase in CRS in the first 12–24 months after diagnosis was objectified in other lymphomas, in which the prognostic effect of EFS24 is more pronounced than in FL 3 , 4 , 9 , 10 . Therefore, the proper validation of EFS24 in FL patients at the population-level is an area for future research.…”
mentioning
confidence: 99%
“…This nomogram was subsequently developed and validated for TTFT (Molica et al , ), implying a connection between TTFT and OS. More recently, analysis of nearly 20 000 TN CLL patients in the Surveillance, Epidemiology, and End Results (SEER) database showed a correlation between shortened TTFT and decreased 5‐year OS (Ammann et al , ). Among TN patients with CLL, TTFT is a disease‐specific endpoint that better reflects the intrinsic biological makeup of the disease, which is independent of the efficacy of treatments, non‐CLL related deaths and treatment‐induced clonal evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Follow‐up for this cohort was not long enough to determine the overall survival (OS) associations with the 29 genes tested because 86% of the samples were assayed in 2016 and 2017 and have a short duration of follow‐up. However, the large cohort of treatment‐naive (TN) patients enabled us to explore time‐to‐first treatment (TTFT) from diagnosis, an important endpoint for untreated CLL patients (Wierda et al , ; Molica et al , ; Wierda et al , ; Gentile et al , ; Ammann et al , ). Furthermore, using TTFT can help to identify early drivers of disease, which may be masked when investigating long‐term and treatment‐defined outcomes, such as progression‐free survival (PFS) and OS.…”
mentioning
confidence: 99%
“…In this study, we performed machine-learning based Gaussian mixture model clustering on a subgroup of genes significantly associated with TTT in order to identify transcriptional clusters with clinical implications. We studied TTT due to the lack of treatment uniformity in the International Cancer Genome Consortium (ICGC) CLL cohort and because it is a variable associated with overall survival (17). We tested our results on a 196 patient cohort and validated its clinical significance in an independent 79 patient cohort.…”
Section: Introductionmentioning
confidence: 99%